2015
DOI: 10.1038/ncomms8829
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, molecular and physiological basis of variation in Drosophila gut immunocompetence

Abstract: Gut immunocompetence involves immune, stress and regenerative processes. To investigate the determinants underlying inter-individual variation in gut immunocompetence, we perform enteric infection of 140 Drosophila lines with the entomopathogenic bacterium Pseudomonas entomophila and observe extensive variation in survival. Using genome-wide association analysis, we identify several novel immune modulators. Transcriptional profiling further shows that the intestinal molecular state differs between resistant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
83
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 57 publications
12
83
2
Order By: Relevance
“…suggested before [11]. We also found differential gene expression patterns among susceptible and resistant colony phenotypes, comparable with recent studies in Drosophila [22,31]. The recipient effect on the immune response may indicate inherent differences between the two genetic host resistance backgrounds in their ability to impose selection on the establishing community.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…suggested before [11]. We also found differential gene expression patterns among susceptible and resistant colony phenotypes, comparable with recent studies in Drosophila [22,31]. The recipient effect on the immune response may indicate inherent differences between the two genetic host resistance backgrounds in their ability to impose selection on the establishing community.…”
Section: Discussionsupporting
confidence: 73%
“…Nevertheless, if hosts have the ability to influence the establishment of the microbiota via the host immune system, we expect to find variation in the immune response towards different classes of microorganisms (i.e. beneficial and non-beneficial), and among the hosts themselves [21,22], similar to the variation in gene expression that underlies the specificity of host-parasite interactions [17,23]. Additionally, in different environments (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This study suggested that the Eiger-mediated immune response aided in the clearance of extracellular pathogens; however, mortality from intracellular-pathogen challenge was unchanged or reduced in Eiger mutants. Drosophila has also been used to reveal virulence factors associated with Francisella tularensis pathogenesis (34), gut immunocompetence during Pseudomonas entomophila infection (41), and phagocytic activity during Mycobacterium marinum infection (32). Taking the data together, the use of Drosophila to investigate bacterial pathogenesis and host immune responses identifies key signaling mechanisms that may lead to the development of novel therapeutics designed to control infection in natural hosts.…”
mentioning
confidence: 99%
“…Importantly, the use of Drosophila allows assessing the impact of different infection states (i.e. no, mild, or severe infection) on distinct, but constant genetic backgrounds through the use of inbred fly lines [56 ]. In addition, it is proving an ideal model to study the molecular and physiological role of the intestinal microbiota in post-embryonic development and homeostasis [57][58][59].…”
Section: Discussionmentioning
confidence: 99%